Metamorfosis Gastronomi Dalam Karya Sastra Kuliner - I Made Suyasa; Linda Ayu Darmurtika (Universitas Muhammadiyah Mataram, 2023)
Abstrak. Tulisan ini merupakan hasil kajian pustaka tentang gastronomi sebagai disiplin yang memayungi kajian karya sastra kuliner yang banyak kita temukan dalam berbagai genre sastra Indonesia. Kuliner menyangkut tempat asal jenis makanan yang disiapkan, baik lokal maupun manca negara. Kuliner banyak dikenal melalui karya sastra dan storinomic yang dibaca. Gastronomi sastra dengan padanan istilah gastrocriticism atau dalam bahasa Indonesia dikenal dengan istilah gastrokritik sastra yang merupakan paduan dari gastronomi dengan literarycriticism/ literary studies. Gastronomi yang dikenal sebagai satu bidang yang mengurusi tentang makanan atau tataboga, sedangkan kritik sastra/kajian sastra merupakan bidang yang mengurusi karya sastra dalam konteks pemahaman. Paduan keduanya melahirkan bidang kajian atau kritik sastra yang lebih tercurah pada karya-karya sastra yang kaya imajinasi dalam nuansa budaya kuliner. Tujuan tulisan ini mengidentifikasi berbagai bentuk metamorfosis gastronomi dalam karya sastra kuliner dan mencermati lebih dekat perkembangan kajiannya. Karya sastra kuliner hadir dalam berbagai genre sastra seperti, puisi, cerpen, novel, dan juga drama. Pendekatan gastronomi sastra atau gastrokritik dapat menjadi kajian dalam membedah karya sastra kuliner. Untuk itu, diharapkan para pemerhati sastra khususnya para akademisi dapat menaruh perhatiannya dalam kajian sastra kuliner Indonesia yang begitu kaya dengan cerminan budaya nusantara.Abstract: This paper is the result of a literature review of gastronomy as a discipline that overshadows the study of culinary literature that we find in various genres of Indonesian literature. Culinary concerns the place of origin of the type of food prepared, both local and foreign. Culinary is widely known through literary and storinomic works that are read. Literary gastronomy with the equivalent of the term gastrocriticism or in Indonesian known as literary gastrocriticism which is a combination of gastronomy with literarycriticism / literary studies. Gastronomy is known as a field that deals with food or tataboga, while literary criticism / literary studies is a field that deals with literary works in the context of understanding. The combination of the two gave birth to the field of study or literary criticism which is more devoted to literary works that are rich in imagination in the nuances of culinary culture. The purpose of this paper is to identify various forms of gastronomic metamorphosis in culinary literature and take a closer look at the development of their studies. Culinary literary works are present in various literary genres such as, poetry, short stories, novels, and also dramas. The literary gastronomic approach or gastrocriticism can be a study in dissecting culinary literary works. For this reason, it is hoped that literary observers, especially academics, can pay attention to the study of Indonesian culinary literature which is so rich in reflections of the culture of the archipelago. .